Fremtidens socialpædagogik - Hanne Meyer-Johansen (Tidsskrift for Professionsstudier)
The article advocates for a more socially transformative and non-individual-oriented approach to social pedagogy, emphasizing the potential of the empowerment concept in efforts to contribute to individuals' emancipation and the transformation of their life conditions. The significance of this pedagogical aim is examined based on an exploration of the historical development of social pedagogy as a normative and political foundational idea, inspired by two central pedagogical and learning theorists: Paulo Freire and Oskar Negt. Drawing on these critical social analyses and transformative possibilities, illustrative examples from previous studies of social pedagogical practice are included to uncover the presence or absence of educators' reflections on critical social and transformative perspectives and transgressive orientations. The prevailing societal tendency towards an individualized and organizationally internal perspective is revealed to dominate, with the reduced social pedagogical potential inherent in such a compensatory view of citizens. However, another study indicates that the need for pedagogical encounters across the organizational frameworks of the workplace can highlight the importance of a broader societal perspective, with solidaristic identification and a focus on the empowerment of the citizens involved. This might be a useful way to contribute to a renewed generation of meaning and a transformative dimension of social pedagogical work, as well as its practitioners in this field.